High pressure nozzle guide vane cooling system flow characteristics - Cresci, I (2016)
The continuous demand from the airlines for reduced jet engine fuel consumption results in increasingly challenging high pressure turbine nozzle guide vane (NGV) working conditions. The capability to reproduce representative boundary conditions in a rig at the combustor-turbine interaction plane is a key feature when testing NGVs in an engine-representative environment. A large scale linear cascade rig to investigate NGV leading edge cooling systems has been designed with particular attention being paid to creating engine representative conditions at the NGV inlet plane. The combustor simulator replicates the main features of a rich-burn design including large dilution jets and extensive endwall film cooling. CFD simulations have been used to develop the design which matches Reynolds number and mainstream-to-dilution jet momentum flux ratio. Detailed measurements of velocity, turbulence and temperature have been acquired at the NGV inlet plane. A thermo-couple was manufactured from 12.7 μm diameter wire and carefully calibrated to obtain its time constant in the velocity range of interest. The results are compared to CFD predictions and data in the literature. The time-averaged measurements show that the flow field conditions are dominated by the endwall cooling flows. The time-resolved data show that the measured turbulence length scale reflects the scale of the relevant upstream jets while the spectrum of temperature fluctuations reports a thermal cascade independent of any geometrical features. Attention was also focused on the flow field downstream of different endwall film cooling holes configurations: three arrangements of a double row of staggered cylindrical holes (lateral pitch-to-diameter ratio of 2 - 3 - 6) and one with intersecting holes (intersecting angle of 90o) were experimentally and numerically analyzed. The research quantified the extent by which closer spaced hole configurations provide more effective film coverage. It was found that the turbulent integral length scales are strongly connected to the hole diameter and spacing. It was also found that intersecting holes can potentially reduce the amount of required coolant at a fixed pressure ratio, but offer worst film performance than cylindrical holes. RANS simulations proved successful at predicting the main trends shown by the measurements. A new concept to increase the pressure margin across the film cooling holes in a specific region of vane LE coolant passage was introduced and developed: an insert was used to cover the area with the highest risk of ingestion, slowing down the flow and increasing the local static pressure. Numerical simulations were initially used to compare different designs and to analyse the impact of the insert on the overall coolant flow distribution. In particular, the effect on the static pressure downstream of the insert was identified as a critical factor that needs to be taken into account during the design process in order to avoid hot gas ingestion in other areas. The experimental campaign proved the ability of this new design to significantly increase the pressure margin in the covered region.